2016
DOI: 10.1039/c6sc00694a
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of nucleic acid molecular aggregates catalyzed by a triple-helix probe for miRNA detection and single cell imaging

Abstract: We developed a new and highly sensitive method for miRNA detection and intracellular imaging based on novel nucleic acid molecular aggregates self-assembled on graphene oxide nanoplates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…The fluorescence intensity has a linear correlation with the logarithm of let-7d concentration from 10 −13 to 10 −9 M. The standard curve equation is F’ = 10462 + 751 logC with a correlation coefficient of 0.9971, where C and F’ are the concentration of let-7d and the fluorescence intensity (F’ = F-F0), respectively. The detection limit is calculated to be 1.5 × 10 −13  M, according to the 3σ rule, which is much lower than that of the existing signal amplification in our previous report34. Moreover, the result was comparable with other amplification methods and the comparison of different methods for miRNA detection is shown in Table S1.…”
Section: Resultsmentioning
confidence: 48%
“…The fluorescence intensity has a linear correlation with the logarithm of let-7d concentration from 10 −13 to 10 −9 M. The standard curve equation is F’ = 10462 + 751 logC with a correlation coefficient of 0.9971, where C and F’ are the concentration of let-7d and the fluorescence intensity (F’ = F-F0), respectively. The detection limit is calculated to be 1.5 × 10 −13  M, according to the 3σ rule, which is much lower than that of the existing signal amplification in our previous report34. Moreover, the result was comparable with other amplification methods and the comparison of different methods for miRNA detection is shown in Table S1.…”
Section: Resultsmentioning
confidence: 48%
“…F‐PNA could induce fluorescence quenching but F‐PNA/RCAP could attenuate the quenching of F‐PNA fluorescence due to adsorption and desorption on the surface of GO. Zhang and co‐workers also used this powerful method to design a system that could clearly distinguish cancer cells from normal cells . To realize naked eye detection, Zhu et al developed a new RGO‐assisted RCA amplification strategy to detect miRNA single nucleotide polymorphisms (SNPs); miR‐125a, let‐7a, their single base mutants and other specific mutants were adopted as models for this study, as shown in Figure B.…”
Section: State‐of‐the‐art Protocols For High‐quality Mirna Detectionmentioning
confidence: 99%
“…Zhang and co-workers also used this powerful method to design a system that could clearly distinguish cancer cells from normal cells. [119] To realize naked eye detection, Zhu et al [120] developed a new RGO-assisted RCA amplification strategy to detect miRNA single nucleotide polymorphisms (SNPs); miR-125a, let-7a, their single base mutants and other specific mutants were adopted as models for this study, as shown in Figure 8B. Compared with the traditional PRC technology, the selectivity of RGO-assisted RCA was greatly improved, and the miRNA SNP signal was as high as 100-fold that of the control signal.…”
Section: Fluorescence Detection With Enzyme Participationmentioning
confidence: 99%
“…[40] In RT-PCR, atarget RNAofinterest is first reverse transcribed into complementary DNA(cDNA) transcripts by reverse transcriptase.T hen, the newly-produced cDNAi s amplified through traditional PCR in the presence of thermostable polymerase,r esulting in indirect amplification-based detection of the target RNA. [44][45][46][47][48][49][50][51][52][53] In FISH, enzymes that can catalyze the amplification of nucleic acid under ambient temperature are generally transferred into cells,t hen the target nucleic acid of interest is amplified, leading to af luorescence signal. [41][42][43] In addition, isothermal enzymatic signal amplificationbased fluorescence in situ hybridization (FISH) assay has been developed for single-cell RNAi maging.…”
Section: Traditional Amplification-based Detection Of Rnamentioning
confidence: 99%